Growth, fatty, and amino acid profiles of the soil alga Vischeria sp. E71.10 (Eustigmatophyceae) under different cultivation conditions - Remias, Daniel; Nicoletti, Cecilia; Krennhuber, Klaus; Möderndorfer, Bettina; Nedbalová, Linda; Procházková, Lenka (Folia microbiologica, 2020)
In this study, a unicellular soil alga isolated from farmland in Germany was surveyed. The investigation of the hypervariable molecular markers ITS1 rDNA and ITS2 rDNA identified strain E71.10 as conspecific with Vischeria sp. SAG 51.91 (Eustigmatophyceae). The culture was tested for biomass generation and for the yield of fatty acids and amino acids. The survey included four different culture conditions (conventional, elevated CO2, nitrogen depletion, or sodium chloride stress) at room temperature. The best yield of dry biomass was achieved applying 1% CO2, whereas nitrogen-free medium resulted into least growth. The fatty acid content peaked in nitrogen-free medium at 59% per dry mass. Eicosapentaenoic acid was the most abundant fatty acid in all treatments (except for nitrogen free), accounting for 10.44 to 16.72 g/100 g dry mass. The highest content of amino acids (20%) was achieved under conventional conditions. The results show that abiotic factors strongly influence to which extent metabolites are intracellularly stored and they confirm also for this yet undescribed strain of Vischeria that Eustigmatophyceae are promising candidates for biotechnology.
Keywords: mastné kyseliny; Germany; ribozomální DNA; DNA, Ribosomal; Nitrogen; Biomass; Fatty Acids; kyselina eikosapentaenová; Stramenopiles; mikrořasy; Eicosapentaenoic Acid; Německo; Culture Media; biotechnologie; kultivační média; Heterokontophyta; Amino Acids; Soil; půda; aminokyseliny; biomasa; Biotechnology; Microalgae; dusík